Effects of a drug overdose in a television drama on presentations to hospital for self poisoning: time series and questionnaire study. - Hawton, K; Simkin, S; Deeks, J; O'Connor, S; Keen, A; Altman, D; Philo, G; Bulstrode, C (1999)
OBJECTIVES: To determine whether a serious paracetamol overdose in the medical television drama Casualty altered the incidence and nature of general hospital presentations for deliberate self poisoning. DESIGN: Interrupted time series analysis of presentations for self poisoning at accident and emergency departments during three week periods before and after the broadcast. Questionnaire responses collected from self poisoning patients during the same periods. SETTING: 49 accident and emergency departments and psychiatric services in United Kingdom collected incidence data; 25 services collected questionnaire data. SUBJECTS: 4403 self poisoning patients; questionnaires completed for 1047. MAIN OUTCOME MEASURES: Change in presentation rates for self poisoning in the three weeks after the broadcast compared with the three weeks before, use of paracetamol and other drugs for self poisoning, and the nature of overdoses in viewers of the broadcast compared with non-viewers. RESULTS: Presentations for self poisoning increased by 17% (95% confidence interval 7% to 28%) in the week after the broadcast and by 9% (0 to 19%) in the second week. Increases in paracetamol overdoses were more marked than increases in non-paracetamol overdoses. Thirty two patients who presented in the week after the broadcast and were interviewed had seen the episode-20% said that it had influenced their decision to take an overdose, and 17% said it had influenced their choice of drug. The use of paracetamol for overdose doubled among viewers of Casualty after the episode (rise of 106%; 28% to 232%). CONCLUSIONS: Broadcast of popular television dramas depicting self poisoning may have a short term influence in terms of increases in hospital presentation for overdose and changes in the choice of drug taken. This raises serious questions about the advisability of the media portraying suicidal behaviour.